Access Forms & Reports for Dummies - Underdahl, Brian (Wiley Publishing, 2011)
'Access Forms Reports For Dummies' is aimed at users with at least some Access experience people who currently use Access, but are not getting as much from it as it promises. It is also for people who have used Excel as a database application and are moving to Access for the more advanced features that it offers - specifically the forms and reports that are so difficult to create in Excel. This book shows readers how to create queries, forms, and reports and make better use of them so that Access becomes the tool that they need. More specifically, it explains how to create queries that make forms and reports more useful; create well-designed forms that enable users to quickly find, enter, and edit data in either a single table or multiple tables with ease; and create reports that present the data in a clearly understandable fashion with effective results.